Genotypic variation of plant biomass under nitrogen deficiency is positively correlated with conservative economic traits in wheat. (13th December 2021) - Huang, Guanjun; Fang, Qing; Peng, Shaobing; Li, Yong
Abstract: Plant functional traits, including leaf and root economic traits, are important for understanding the composition and function of ecosystems. However, plant functional traits of crop species and the relationships between them, and their responses to environmental variations are not fully understood. In the present study, the traits in the leaf and root economics spectrum (LES and RES) and plant biomass were investigated in 14 wheat genotypes grown with sufficient or limited nitrogen (N) supply. We found that N had significant impacts on the LES and RES traits and on the relationships among them. Our results generally supported the hypothesized LES, but did not support the RES or plant economics spectrum concept among wheat plants regardless of N treatment. More importantly, we found that more conservative leaf and root economic traits are beneficial for shoot biomass accumulation in wheat plants grown with limited N supply, and for the improvement in the tolerance of wheat to N stress. The data presented suggest that growth conditions should be accounted for when studying trait-to-trait relationships, and that more conservative resource use strategies could be used as promising targets for wheat breeding programs with limited N input. Abstract : Growth conditions should be accounted for when studying trait-to-trait relationships, and more conservative economic traits could improve biomass production and N stress tolerance of wheat plants under N-deficient conditions.